Monitoring acclimatization and training responses over 17-21 days at 1,800 m in elite cross-country skiers and biathletes - Karlsson, Ø.; Laaksonen, M. S.; McGawley, K. (Frontiers in Sports and Active Living, 2022)
Objective: To monitor the daily variations and time course of changes in selected variables during a 17-21-day altitude training camp at 1,800 m in a group of elite cross-country skiers (9 women, 12 men) and biathletes (7 women, 4 men).